Dogs Barking and Babies Crying: The Effect of Environmental Noise on Physiological State and Cognitive Performance - Ana Arruda; Carolina Mesquita; Rodrigo Couto; Vanessa Sousa; Catarina Mendonça (Noise and Health)
Objective: The exposure to some environmental sounds has detrimental effects on health and might affect the performance in cognitive tasks. In this study, we analyze the effect of the neighborhood noises of a baby crying and dogs barking on the autonomic response and cognitive function. Materials and methods: Twenty participants were exposed, in separate sessions, to white noise, a baby crying, a small dog barking, and a large dog barking. During each session, heart rate, skin conductance, reaction times, spatial memory, and mathematical processing measures were taken throughout time. Results: The sounds of a baby crying and dogs barking led to significantly higher heart rates and skin conductance levels as opposed to exposure to white noise. Results were not as consistent with exposure to barking as they were to the baby. Exposure to the baby crying and dogs barking led to faster reaction times, possibly due to a facilitation by the autonomic system activation. No significant effects on spatial memory were found. Conversely, participants performed worse and slower in a mathematical task when exposed to the dog and baby sounds, than when exposed to control noise. Conclusion: Exposure to the sound of crying babies and dogs barking leads to increased sympathetic response and decreased cognitive ability, as compared to exposure to control sounds. Special attention should be paid to the mitigation of exposure to these types of noises.